Al doped hematite nanoplates: Structural and Raman investigation. Issue 6 (15th March 2022) - Pattanayak, Namrata; Panda, Padmalochan; Parida, Santanu
Abstract: We report on the influence of Al doping on the structural, morphological and vibrational properties of hematite crystallite synthesized by using the hydrothermal method. The structural property of the pristine and Al doped hematite samples are extensively characterized by the Rietveld profile refinement of X-ray diffraction data. The structural refinement suggests that both the pristine and the doped compounds are stabilized in the hexagonal R 3 ̄ c symmetry. Doping with Al induces a compressive strain in the hematite lattice, which is further reflected in the spectroscopic Raman studies. It is also observed that the Al atom has a significant influence on the growth mechanism of hematite crystallites. Temperature dependent Raman study performed in the Al doped hematite sample brings out anomalous behaviour of phonon modes and line widths around the temperature region of 150 K. These anomalies observed around the temperature region of 150 K are suggestive of the presence of spin-phonon coupling associated with the Morin transition in the Al doped hematite. Our detailed structural and Raman spectroscopic analyses suggest that the Al doped hematite can be a potential magnetodielectric candidate.